A randomised comparative study of the effect of Airtraq optical laryngoscope vs. Macintosh laryngoscope on intraocular pressure in non-ophthalmic surgery - Das,Bikramjit (2016)
BACKGROUND: We compared intraocular pressure changes following laryngoscopy and intubation with conventional Macintosh blade and Airtraq optical laryngoscope. METHODS: Ninety adult patients were randomly assigned to study group or control group. Study group (n = 45) - Airtraq laryngoscope was used for laryngoscopy. Control group (n = 45) - conventional Macintosh laryngoscope was used for laryngoscopy. Preoperative baseline intraocular pressure was measured with Schiotz tonometer. Laryngoscopy was done as per group protocol. Intraocular pressure and haemodynamic parameters were recorded just before insertion of the device and subsequently three times at an interval of one minute after insertion of the device. RESULTS: Patient characteristics, baseline haemodynamic parameters and baseline intraocular pressure were comparable in the two groups. Following insertion of the endotracheal tube with Macintosh laryngoscope, there was statistically significant rise in heart rate and intraocular pressure compared to Airtraq group. There was no significant change in MAP. Eight patients in Macintosh group had tongue-lip-dental trauma during intubation, while only 2 patients received upper airway trauma in Airtraq group. CONCLUSION: We conclude that Airtraq laryngoscope in comparison to Macintosh laryngoscope results in significantly fewer rises in intraocular pressure and clinically less marked increase in haemodynamic response to laryngoscopy and intubation.